Investigating English Language Teachers’ Opinions on the Implementation of the EAN Program - Tsolou, Olympia (Advances in Social Sciences Research Journal, 2026)
The introduction of the English language in the Greek preschool education through the EAN program represents an innovative educational initiative aimed at enhancing both the methodological and thematic aspects of the Preschool Curriculum. This initiative focuses on the linguistic, cognitive, and communicative development of students of this age group, while also promoting multiculturalism, multilingualism, awareness and acceptance of diversity. Additionally, the program encourages interdisciplinary approaches and differentiated pedagogy. The current study examines English language teachers’ opinions on the implementation of the EAN program during the 2023-2024 school year, two years after its nationwide rollout in all preschools. It gathers feedback from English teachers in preschools across the B and D Primary Education Directorates of Athens, exploring their perspectives on specific methodological areas and teaching parameters of the EAN program, particularly the educational material. The research is original and highlights the strengths of the EAN program and its educational material, and areas that need improvement.